ASSESSING THE IMPACT OF RISK MANAGEMENT COMPONENTS ON CONSTRUCTION PROJECT PERFORMANCE IN MOROGORO MUNICIPAL COUNCIL, TANZANIA - Aurelia Ngirwa Kamuzora (Acta Economica)
This study examines the impact of risk management components on the performance of construction projects in Morogoro Municipal Council, Tanzania. Data from 162 employees of contractors reveal that 33% hold postgraduate degrees, while 67% have qualifications below this level. Additionally, 42% have over five years of project management experience, and only 20% are proficient in risk management. Logistic regression analysis explored the relationships between Project Risk Identification, Project Risk Analysis, Project Risk Control, and construction project performance. The correlation matrix shows strong positive correlations between these risk management components and project performance, suggesting that effective risk management practices lead to better project outcomes. The model summary indicates a strong positive correlation (R = 0.862) between the predictors and the dependent variable, with an R-Square value of 0.749, meaning that approximately 75% of the variability in project performance is explained by the model. Logistic regression coefficients highlight the significant impact of Project Risk Identification (β = 0.303), Project Risk Analysis (β = 0.398), and Project Risk Control (β = 0.560). In conclusion, this study emphasises the importance of comprehensive risk management practices in enhancing construction project performance in Morogoro Municipal Council. These findings provide valuable insights for practitioners and policymakers in construction project management.